2004
DOI: 10.1073/pnas.0401809101
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the Rhesus protein Rh1 impairs growth of the green alga Chlamydomonas reinhardtii at high CO 2

Abstract: Although Rhesus (Rh) proteins are best known as antigens on human red blood cells, they are not restricted to red cells or to mammals, and hence their primary biochemical functions can be studied in more tractable organisms. We previously established that the Rh1 protein of the green alga Chlamydomonas reinhardtii is highly expressed in cultures bubbled with air containing high CO 2 (3%), conditions under which Chlamydomonas grows rapidly. By RNA interference, we have now obtained Chlamydomonas rh mutants (epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 56 publications
3
138
0
Order By: Relevance
“…Such a role was suggested based on reduced growth of green algae following sRNAi down regulation of a native Rh homolog (34,35). Support for this proposal was augmented by a feature of the prokaryotic NeRh structure (16), where a CO 2 binding site was identified in a cleft near the cytosolic aperture of the channel.…”
Section: Resultsmentioning
confidence: 99%
“…Such a role was suggested based on reduced growth of green algae following sRNAi down regulation of a native Rh homolog (34,35). Support for this proposal was augmented by a feature of the prokaryotic NeRh structure (16), where a CO 2 binding site was identified in a cleft near the cytosolic aperture of the channel.…”
Section: Resultsmentioning
confidence: 99%
“…However, based on the relatively restricted organ and tissue distribution of Rh proteins and the observation that mutants of Chlamydomonas reinhardtii lacking the paralogue Rh1 protein grow very slowly under high CO 2 conditions, these authors further suggested that mammalian Rh proteins might function as CO 2 rather than as NH 3 gas channels [42,43]. Although the narrowness of the channel in AmtB and the nature of the porelining amino acids [30,31] do not favour the hypothesis of a CO 2 transporter, we cannot formally rule out that Rh glycoproteins are gas channels that might facilitate either NH 3 or CO 2 transport depending on which cell types they are expressed in.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was also proposed recently that the Rh1 protein paralog of the green alga Chla- mydomonas reinhardtii might be regarded as a gas channel for CO 2 , because mutants lacking this protein grow only very slowly when cultured in high CO 2 conditions (48). That Rh proteins might transport NH 3 and͞or CO 2 is a possibility that should be further explored (32).…”
Section: Ch3nh2͞nh3 Transport Function Is Mediated By a Protein-depenmentioning
confidence: 99%